The Aβ42:Aβ40 ratio modulates aggregation in beta-amyloid oligomers and drives metabolic changes and cellular dysfunction - Haessler, Annika; Gier, Stefanie; Jung, Nathalie; Windbergs, Maike (Frontiers in Cellular Neuroscience, 2024)
The pathophysiological role of Aβ42 oligomers in the onset of Alzheimer's disease (AD) is heavily disputed, pivoting research towards investigating mixed oligomers composed of Aβ42 and Aβ40, which is more abundant but less aggregation-prone. This study investigates Aβ42:Aβ40 oligomers in different ratios, examining their adverse effects on endothelial cells, neurons, astroglia, and microglia, as well as in a human blood-brain barrier (BBB) model. Combining label-free Raman microscopy with complementary imaging techniques and biochemical assays, we show the prominent impact of Aβ40 on Aβ42 fibrillation, suggesting an inhibitory effect on aggregation. Mixed oligomers, especially with low proportions of Aβ42, were equally detrimental as pure Aβ42 oligomers regarding cell viability, functionality, and metabolism. They also differentially affected lipid droplet metabolism in BBB-associated microglia, indicating distinct pathophysiological responses. Our findings demonstrate the overarching significance of the Aβ42:Aβ40 ratio in Aβ oligomers, challenging the traditional focus on Aβ42 in AD research.